The Modern British Artist as Printmaker : The Post-War Years. (London : Austin/Desmond Contemporary Books, 1989)
Bellamy, John ; Blake, Peter ; Butler, Reg ; Chadwick, Lynn ; Davie, Alan ; Frost, Terry ; Hepworth, Barbara ; Heron, Patrick ; Hilton, Matthew ; Hilton, Roger ; Hockney, David ; Hoyland, John ; Kitaj, R.B. ; etc.
The Modern British Artist as Printmaker : The Post-War Years, Austin/Desmond Contemporary Books, London, 1989
boek
Keywords: Groot-Brittannië